Bentuk Pertanggungjawaban Pemerintah Terhadap Lumpuhnya Pusat Data Nasional Berdasarkan Hukum Administrasi Negara - Husein Muhammad Iqbal; Sapto Hermawan; Asianto Nugroho (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study examines the government's accountability for the collapse of the National Data Center (Pusat Data Nasional, PDN) due to a cyber attack from an Administrative Law perspective. The increasing reliance on digital technology has made e-government systems more vulnerable to cyber threats, as evidenced by the PDN Surabaya incident in June 2024. The objective of this research is to analyze the government's responsibility in safeguarding personal data and ensuring the continuity of public services. This study explores key legal frameworks, including the Personal Data Protection Law, Presidential Regulations on the Electronic-Based Government System (Sistem Pemerintahan Berbasis Elektronik, SPBE), and other relevant regulations governing cybersecurity and administrative responsibility.The research employs a normative legal research method with a statutory approach, analyzing legal provisions and their application in addressing cyber incidents affecting government-operated databases. The findings reveal that the government can be held accountable through various administrative measures, including the imposition of administrative sanctions, mandatory public notifications, and legal proceedings in administrative courts. However, the study also identifies significant challenges in implementing these measures due to the absence of a dedicated supervisory agency responsible for overseeing the security and resilience of e-government infrastructure. The lack of clear mechanisms for enforcement further complicates accountability efforts.Therefore, this study highlights the urgency of strengthening cybersecurity governance, establishing an independent supervisory body, and enhancing legal frameworks to ensure better protection of personal data and the reliability of digital public services. By addressing these gaps, the government can improve public trust and minimize future cyber risks.